2010
DOI: 10.1177/1090198109349218
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Ecodevelopmental Theory in Predicting HIV Risk Behaviors Among Hispanic Youth

Abstract: Ecodevelopmental theory is a theoretical framework used to explain the interplay among risk and protective processes associated with HIV risk behaviors among adolescents. Although ecodevelopmentally based interventions have been found to be efficacious in preventing HIV risk behaviors among Hispanic youth, this theory has not yet been directly empirically tested through a basic research study in this population. The purpose of this cross-sectional study was to empirically evaluate an ecodevelopmentally based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 61 publications
8
102
0
Order By: Relevance
“…Accordingly, a chronological chain of developmental task resolutions is key for adaptive development, whereas disruption of this sequence poses threats to normative development and places one at risk for psychopathology. Stress associated with cultural adaption, for example, can exert significant and potentially deleterious effects on adolescent development (Prado et al 2010). Specifically, bicultural stress may interrupt normative successive developmental processes, such as the development of personal identity, that are key in promotion of effective adaptation to new environments and challenges (Roisman et al 2004).…”
Section: A Developmental Psychopathology Perspectivementioning
confidence: 99%
“…Accordingly, a chronological chain of developmental task resolutions is key for adaptive development, whereas disruption of this sequence poses threats to normative development and places one at risk for psychopathology. Stress associated with cultural adaption, for example, can exert significant and potentially deleterious effects on adolescent development (Prado et al 2010). Specifically, bicultural stress may interrupt normative successive developmental processes, such as the development of personal identity, that are key in promotion of effective adaptation to new environments and challenges (Roisman et al 2004).…”
Section: A Developmental Psychopathology Perspectivementioning
confidence: 99%
“…Pantin, Schwartz, Sullivan, Prado, & Szapocznik, 2004), including substance use initiation. For example, ecodevelopmental theory has been tested empirically by Prado and colleagues (2010) to examine HIV risk behaviors among Hispanic youth. This study found that the parent-adolescent acculturation gap and the parent's U.S. acculturation orientation had indirect effects on these behaviors through risk and protective factors related to family functioning, academic functioning, and peers.…”
Section: Introductionmentioning
confidence: 99%
“…Ecodevelopmental theory (Pantin et al, 2004; Prado et al, 2010; Szapocznik & Coatsworth, 1999; Schwartz, Coatsworth, Pantin, & Szapocznik, 2003) integrates three key elements (social-ecological theory, social interactions, and developmental theory) to help understand the factors associated with adolescent risk and protection. Social-ecological theory (Bronfenbrenner, 1979) proposes that the multiple factors influencing adolescent development can be organized within four social contexts: macrosystem, exosystem, mesosystem, and microsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Some research suggests that such cultural discrepancies might become sources of parent-child conflict (Bámaca-Colbert & Gayles, 2010;Cervantes, Fisher, Córdova, & Napper, 2012;Szapocznik & Kurtines, 1993). Parent-child conflict is relevant to family science because it shapes parent-child relationships, parenting practices, family dynamics, and developmental outcomes (Prado et al, 2010;Santisteban, Coatsworth, Briones, Kurtines, & Szapocznik, 2012).…”
Section: "Our Child Is Not Like Us:" Understanding Parent-child Conflmentioning
confidence: 99%